Chaff Cloud Modeling and Electromagnetic Scattering Properties Estimation - Jun-Seon Kim; Dong-Yeob Lee; Tae-Hyeong Kim; Dong-Wook Seo (IEEE Access, 2023)
Chaff is a radar countermeasure used to interfere with ground radar detection or missile target detection by disrupting the radar. As radar is essential in modern electronic warfare, chaff is also essentially used in many military vehicles. A large amount of chaffs in the form of a thin and long wire is contained in a cylindrical or rectangular cartridge and is launched to form a chaff cloud to disturb the radar. It is virtually impossible to examine the chaff cloud analytically because it is released at once into the air in large quantities. Therefore, for chaff cloud analysis, an approximation method or statistical characteristics are used, or real data is measured directly through experiments. The study of chaff consists of two parts: chaff cloud modeling, which determines the dynamic characteristics of chaff, and estimation of electromagnetic scattering properties, which determines the signal characteristics of the chaff. This review paper focuses on the techniques used in chaff cloud modeling and the estimation of electromagnetic scattering properties. We categorized the techniques by statistical, numerical, and empirical methods. In chaff cloud modeling, studies for the purpose of scattering analysis generally use typical distribution, whereas if chaff cloud modeling itself is the purpose, it is aimed at realizing a realistic chaff cloud by referring to experimental data. For estimation of electromagnetic scattering properties, a conventional method that simply multiplies the average radar cross-section of chaff element to obtain the total radar cross-section of the chaff cloud is used, and a method that allows rapid calculation while considering the distribution of the chaff cloud is being studied.